Quantitative efficiency of optoacoustic ultrasonic treatment in SLM, DED, and LBW applications - Stepan L. Lomaev; Dinara R. Fattalova; Georgii A. Gordeev; Marat A. Timirgazin; Mikhail D. Krivilyov (Scientific Reports)
Abstract Ultrasound can improve the quality of finished products by reducing porosity and enhancing microstructure in selective laser melting, directed energy deposition, and laser beam welding. This study evaluates the efficiency of ultrasound produced by a pulsed laser via the optoacoustic effect. A quantitative model of collapse of vapor-gas bubbles has been developed under the conditions of ultrasonic treatment at near resonance frequencies. Based on the simulation results, the phenomenological expressions are suggested to determine the optimal operating frequency and power for the pulsed laser to alter the microstructure and porosity effectively via cavitation. The analysis is performed for the 316 L stainless steel and titanium Ti-6Al-4 V alloy, which are common in additive manufacturing.